PSYCHOLOGICAL FEATURES OF INDIVIDUAL DIFFERENCES IN PERSONALITY DEVELOPMENT - Zasiekin, Artur (Personality and environmental issues, 2026)
The article examines the psychological features of individual differences in personality development. The relevance of the topic is обусловed by the fact that in modern psychology the problem of individual differences is gaining particular importance due to the need for a deeper understanding of the patterns of personality formation, its unique traits, abilities, temperament, character, and behavioral manifestations. Attention to individual psychological characteristics makes it possible to better explain differences in developmental pace, methods of adaptation, levels of self-realization, and personal growth. The aim of the article is to provide a theoretical analysis of the psychological features of individual differences in personality development and to identify the main factors influencing their formation and manifestation. The article emphasizes that personality development is a complex and multifactorial process in which biological, social, cultural, and psychological determinants are integrated. Individual differences are considered as the result of the interaction between hereditary predispositions, environmental conditions, upbringing, education, life experience, and the activity of the individual. The main approaches to the study of individual differences in psychology are analyzed, particularly in the context of temperament, character, abilities, the emotional-volitional sphere, and motivation. It is emphasized that individual characteristics determine the uniqueness of personality development, behavior, style of activity, and interaction with others. The importance of the differential-psychological approach is highlighted for understanding personality as a unique system of traits and as a subject of its own development. It is concluded that individual differences are an important factor in personality development, as they determine the specificity of psychological formation, adaptation, self-development, and the realization of inner potential. A promising direction for further research is an in-depth study of the relationship between individual psychological characteristics and the social conditions of development, as well as the mechanisms of personal self-realization.